Identification of renal Cd36 as a determinant of blood pressure and risk for hypertension - Pravenec, Michal; Churchill, Paul C; Churchill, Monique C; Viklicky, Ondrej; Kazdova, Ludmila; Aitman, Timothy J; Petretto, Enrico; Hubner, Norbert; Wallace, Caroline A; Zimdahl, Heike; Zidek, Vaclav; Landa, Vladimir; et al. (Nature genetics, 2008)
To identify renally expressed genes that influence risk for hypertension, we integrated expression quantitative trait locus (QTL) analysis of the kidney with genome-wide correlation analysis of renal expression profiles and blood pressure in recombinant inbred strains derived from the spontaneously hypertensive rat (SHR). This strategy, together with renal transplantation studies in SHR progenitor, transgenic and congenic strains, identified deficient renal expression of Cd36 encoding fatty acid translocase as a genetically determined risk factor for spontaneous hypertension.
Keywords: Animals; Rats; lokus kvantitativního znaku; antigeny CD36; potkani inbrední SHR; zvířata; CD36 Antigens; Kidney; Quantitative Trait Loci; Rats, Inbred SHR; Hypertension; krysa rodu Rattus; ledviny; hypertenze